Narrative Review: Assessment of Neisseria gonorrhoeae Infections Among Men Who Have Sex With Men in National and Sentinel Surveillance Systems in the United States. Issue 4 (April 2018) - Weston, Emily J.; Kirkcaldy, Robert D.; Stenger, Mark; Llata, Eloisa; Hoots, Brooke; Torrone, Elizabeth A.
Abstract : Abstract: To assess trends in Neisseria gonorrhoeae among gay, bisexual, and other men who have sex with men (MSM), we reviewed existing and published gonorrhea surveillance data in the United States. Data identified in this review include the following: national gonorrhea case report data and data from 3 other surveillance programs, the Gonococcal Isolate Surveillance Project (GISP), the STD Surveillance Network (SSuN), and National HIV Behavioral Surveillance. Rates of reported cases of gonorrhea among men increased 54.8% in 2006 to 2015 compared with a 2.6% increase among women. Since 2012, the rate of reported gonorrhea cases among men surpassed the rate among women; the male-to-female case rate ratio increased from 0.97 in 2012 to 1.31 in 2015. The proportion of gonococcal urethral isolates collected in the Gonococcal Isolate Surveillance Project that were collected from MSM increased from 21.5% to 38.1% in 2006 to 2015. In 2009 to 2015, the percent of MSM who tested positive for rectal and oropharyngeal gonorrhea in sexually transmitted disease (STD) clinics increased by 73.4% and 12.6%, respectively. Estimated rates of gonorrhea among MSM increased by 151% in 2010 to 2015 in jurisdictions participating in the STD Surveillance Network. Data from the National HIV Behavioral Surveillance demonstrate that testing for gonorrhea among MSM increased by 23.1% between 2011 and 2014. Together, surveillance data suggest a disproportionate burden of gonorrhea among MSM in the United States and suggest increases in both screening and disease in recent years. Because each data source has inherent limitations and biases, examining these data from different systems together strengthens this conclusion. Abstract : A review of 4 data sources suggests that gonococcal diagnoses are increasing among men who have sex with men in the United States.